2023
DOI: 10.1001/jamapediatrics.2022.6243
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Efficacy and Safety of mRNA COVID-19 Vaccines in Children Aged 5 to 11 Years

Abstract: ImportanceEvidence of the efficacy and safety of messenger RNA (mRNA) COVID-19 vaccines in children aged 5 to 11 years has been emerging. Collecting these data will inform clinicians, families, and policy makers.ObjectiveTo evaluate the efficacy and safety of mRNA COVID-19 vaccines in children aged 5 to 11 years in a systematic review and meta-analysis.Data SourcesPubMed and Embase databases were searched on September 29, 2022, without language restrictions.Study SelectionRandomized clinical trials and observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
34
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 81 publications
4
34
0
2
Order By: Relevance
“…Extrapolating this rate to the five to 11 year old population in UK (5 million) and conservatively assuming all would be hospitalised gives a central estimate of 8 hospital admissions due to the vaccine, which we split across UHC and non UHC children 1:7. We note that Watanabe et al report no vaccine-caused deaths among 16.6 million injections [44].…”
Section: %mentioning
confidence: 51%
See 1 more Smart Citation
“…Extrapolating this rate to the five to 11 year old population in UK (5 million) and conservatively assuming all would be hospitalised gives a central estimate of 8 hospital admissions due to the vaccine, which we split across UHC and non UHC children 1:7. We note that Watanabe et al report no vaccine-caused deaths among 16.6 million injections [44].…”
Section: %mentioning
confidence: 51%
“…A systematic review of vaccination for 5-11 year olds reported a myocarditis rate of 1.3-1.8/million vaccinations given [44]. Extrapolating this rate to the five to 11 year old population in UK (5 million) and conservatively assuming all would be hospitalised gives a central estimate of 8 hospital admissions due to the vaccine, which we split across UHC and non UHC children 1:7.…”
Section: %mentioning
confidence: 99%
“…The estimated incidence is about 1 in 50 000 across all age groups but as high as 1 in 6600 in people aged 16 to 19 years . The systematic review and meta-analysis by Watanabe et al found that the incidence of myocarditis in children aged 5 to 11 years was about 1 in 500 000. Fortunately, myocarditis following vaccination is generally short-lived and self-resolving …”
mentioning
confidence: 99%
“…In this issue of JAMA Pediatrics , Watanabe and coauthors evaluated the safety and efficacy of 2 doses of Pfizer’s messenger RNA (mRNA) vaccine in children aged 5 to 11 years during both the delta and omicron waves of COVID-19. In a systematic review and meta-analysis that included 17 published studies of 10 935 541 vaccinated and 2 635 251 unvaccinated children, they found that the mRNA vaccine was effective at preventing SARS-CoV-2 infection, symptomatic infection, hospitalization, and multisystem inflammatory syndrome in children (MIS-C).…”
mentioning
confidence: 99%
See 1 more Smart Citation